Sakura Hime : the legend of Princess Sakura. 3 - Tanemura, Arina; Miyaki, Tetsuichiro (Shojo beat, 2011)
Sakura, still grieving Oumi's death, must fight the powerful youko of Uii. When she finds herself no match for the demon's poisonous vapor, it is time for Kobaku and Hayate, with a little help from the full moon, to step in.